Applications and implications of ecological energetics - Tomlinson, S.; Arnall, S.; Munn, A.; Bradshaw, S.; Maloney, S.; Dixon, Kingsley; Didham, R. (Elsevier, 2014)
The ecological processes that are crucial to an animal's growth, survival, and reproductive fitness have energetic costs. The imperative for an animal to meet these costs within the energetic constraints of the environment drives many aspects of animal ecology and evolution, yet has largely been overlooked in traditional ecological paradigms. The field of 'ecological energetics' is bringing comparative physiology out of the laboratory and, for the first time, is becoming broadly accessible to field ecologists addressing real-world questions at many spatial and temporal scales. In an era of unprecedented global environmental challenges, ecological energetics opens up the tantalising prospect of a more predictive, mechanistic understanding of the drivers of threatened species decline, delivering process-based modelling approaches to natural resource management.